Highlighting the potential of peer-led workshops in training early-career researchers for conducting research with Indigenous communities - Gwyneth A. MacMillan; Marianne Falardeau; Catherine Girard; Sophie Dufour-Beauséjour; Justine Lacombe-Bergeron; Allyson K. Menzies; Dominique A. Henri (Canadian Science Publishing, 2019)
For decades, Indigenous voices have called for more collaborative and inclusive research practices. Interest in community-collaborative research is consequently growing among university-based researchers in Canada. However, many researchers receive little formal training on how to collaboratively conduct research with Indigenous communities. This is particularly problematic for early-career researchers (ECRs) whose fieldwork often involves interacting with communities. To address this lack of training, two peer-led workshops for Canadian ECRs were organized in 2016 and 2017 with the following objectives: (i) to cultivate awareness about Indigenous cultures, histories, and languages; (ii) to promote sharing of Indigenous and non-Indigenous ways of knowing; and (iii) to foster approaches and explore tools for conducting community-collaborative research. Here we present these peer-led Intercultural Indigenous Workshops and discuss workshop outcomes according to five themes: scope and interdisciplinarity, Indigenous representation, workshop environment, skillful moderation, and workshop outcomes. Although workshops cannot replace the invaluable experience gained through working directly with Indigenous communities, we show that peer-led workshops can be an effective way for ECRs to develop key skills for conducting meaningful collaborative research. Peer-led workshops are therefore an important but insufficient step toward more inclusive research paradigms in Canada.